Single-molecule tracking of PprI in D. radiodurans without interference of autoblinking - Zhai, Fanfan; Hao, Li; Chen, Xiaomin; Jiang, Ting; Guo, Qianhong; Xie, Liping; Ma, Ying; Du, Xiaobo; Zheng, Zhiqin; Chen, Kun; Fan, Jun (Frontiers in Microbiology, 2023)
Autoblinking is a widespread phenomenon and exhibits high level of intensity in some bacteria. In Deinococcus radiodurans (D. radiodurans), strong autoblinking was found to be indistinguishable from PAmCherry and greatly prevented single-molecule tracking of proteins of interest. Here we employed the bright photoswitchable fluorescent protein mMaple3 to label PprI, one essential DNA repair factor, and characterized systematically the fluorescence intensity and bleaching kinetics of both autoblinking and PprI-mMaple3 molecules within cells grown under three different conditions. Under minimal media, we can largely separate autoblinking from mMaple3 molecules and perform reliably single-molecule tracking of PprI in D. radiodurans, by means of applying signal-to-noise ratio a thresholding algorithm for localizations and constraining the minimal length for linking the trajectories. We observed three states of PprI molecules, which bear different subcellular localizations and distinct functionalities. Our strategy provides a useful means to study the dynamics and distributions of proteins of interest in bacterial cells with high level of autoblinking.